Western Himalayan Cold Deserts: Biodiversity, Eco-Restoration, Ecological Concerns and Securities - Tewari, V P; Kapoor, K S (Annals of Arid Zone, 2016)
This paper provides an insight into the intimate relationships between plant diversity, land degradation and ecological concerns in the cold deserts, which is a unique eco-system of Western Himalayas. Undoubtedly, addressing desertification, including land, soil, water and plant degradation, can certainly facilitate or ease the ecological concerns, but may not completely solve it in presence of the other issues, related causes and the effects. In view of the fact that very little or for that matter no site specific research work has been done in these fragile but ecologically significant areas, an attempt has been made to offer some suggestions, in the wider context, so as to evolve and develop ecologically and socio-economically sensitive and acceptable strategies for holistic development of the area under reference. Key words: Cold deserts, ecosystem, biodiversity, hot spot, land-use, degradation.